Climate trends and the occurrence of pest outbreaks in the Krasnoyarsk forest-steppe zone - Andronova Alina; Vajs Andrej; Mihajlov Pavel; Nemich Viktor (BIO Web of Conferences)
The article presents an analysis of air temperature and precipitation during the growing season. This period is of significance for all plant species on the planet as it is when their vital functions are actively manifested. The length of the growing season is the primary factor determining the composition of zonal plant communities. The present research examines the dynamics of change in the average temperature during the growing season for the period from 1891 to 2021 in the Krasnoyarsk forest-steppe zone. The data are divided into periods with characteristic temperature features. The results demonstrate an increase in values over time, attributable to changes in precipitation amounts during the growing season. This study presents an analysis of temperature dynamics during the growing season, as well as the growing season's length, from 2002 to 2022. The analysis revealed an increase in the length of the growing season, from 155 days in 2002 to 176 in 2022. Furthermore, the study examined the influence of climate on the occurrence of pest outbreaks and wildfires.